Measuring environmental degradation developing pressure indicators for Europe - Markandya, Anil, 1945-; Dale, Nick, 1960-; Eurostat; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2001)
Measuring environmental degradation is a unique book that provides a comprehensive yet concise overview of the key issues of environmental significance addressed as part of the Eurostat 'Environmental Pressure Indicators Project.' The book is part of the 'Towards environmental pressure indicators for the EU' (TEPI) series that has resulted from the project.
pt. 1. Air pollution -- pt. 2. Climate change -- pt. 3. Loss of biodiversity -- pt. 4. Marine environment and coastal zones -- pt. 5. Ozone layer depletion -- pt. 6. Resource depletion -- pt. 7. Dispersion of toxic substances -- pt. 8. Urban environmental problems -- pt. 9. Waste -- pt. 10. Water pollution and water resources -- pt. 11. Annexes.
"Eurostat."
Includes bibliographical references and index.
Keywords: Environmental degradation -- Europe -- Measurement; Environmental indicators -- Europe; Electronic books